A REAL-TIME LIQUID SURFACE CONTOUR MEASUREMENT SYSTEM IN DYNAMIC TANK USING HC-SR04 ULTRASONIC SENSORS AS A VOLUME CALCULATION INNOVATION - Mukhtarul Amri T, M
In many industries, especially for oil and gas, storage tank is one of the most important instruments in custody transfer and inventory control. Errors of the level measurement in storage tank can cause considerable economic losses. Servo as a measurement instrument that is quite often used in industry today has a slow response to the measurement of dynamic liquids. Also, single point level measurement does not get a representative result of volume calculation of dynamic fluid. For this reason, measurement instrument that have a fast response and be able to measure multi point level is needed. In this study, the measurement of liquid level was implemented using 70 HC-SR04 ultrasonic sensors. All sensors were divided into 5 control areas, each of which was controlled by Arduino Mega 2560. Using PLX-DAQ as data acquisition software, the measurement results were sent directly to Microsoft Excel as an interface that displayed a 3D liquid contours and the results of its volume calculation. Measurement that were implemented on static fluid with 29 ms delay time between two sensors resulted precision above 98% and measurement errors below 4 mm. The system in real time has ran well when tested on water waves in a 2D wave flume tank in wave laboratory of Ocean Engineering ITB.